2019
DOI: 10.1016/j.bja.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Independent discussion sections for improving inferential reproducibility in published research

Abstract: There is a reproducibility crisis in science. There are many potential contributors to replication failure in research across the translational continuum. In this perspective piece, we focus on the narrow topic of inferential reproducibility. Although replication of methods and results is necessary to demonstrate reproducibility, it is not sufficient. Also fundamental is consistent interpretation in the Discussion section. Current deficiencies in the Discussion sections of manuscripts might limit the inferenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 54 publications
0
20
0
1
Order By: Relevance
“…It has been suggested that an independent Discussion for scientific manuscripts can be useful in objectively assessing inferential reproducibility. 5 In Table 1, we provide a structured independent Discussion for the study by Sieber and colleagues, 3 and we comment on the similarities and differences between the original Discussion and the independent Discussion as an example of this approach. The author of the Independent Discussion (PEV) had access only to the manuscript's Introduction, Methods and Results, but not to the Abstract or the Discussion.…”
mentioning
confidence: 99%
“…It has been suggested that an independent Discussion for scientific manuscripts can be useful in objectively assessing inferential reproducibility. 5 In Table 1, we provide a structured independent Discussion for the study by Sieber and colleagues, 3 and we comment on the similarities and differences between the original Discussion and the independent Discussion as an example of this approach. The author of the Independent Discussion (PEV) had access only to the manuscript's Introduction, Methods and Results, but not to the Abstract or the Discussion.…”
mentioning
confidence: 99%
“…24 To address these biases, new peer-review strategies have attracted journals' interest, including double-blind peer review in which authors and their affiliations are concealed from reviewers, open peer review which reveals the full identities of authors and reviewers, and an 'independent' discussion section in which an independent expert who is not an author writes a second discussion. 24,25 These strategies may help to limit poor-quality research entering the public domain. In addition, we strongly recommend that journal editors of non-anesthesia journals obtain peer review from at least one expert obstetric anesthesiologist.…”
Section: Misinformation and The News Mediamentioning
confidence: 99%
“…So, for some papers, the journal now asks independent specialists to write their own discussion. Unlike conventional peer reviewers, they look only at the methods and results sections and are blinded to the paper's conclusions 3 . The two discussions are published together, with similarities and differences highlighted.…”
Section: By Dav I D a Da Mmentioning
confidence: 99%